2016
DOI: 10.1002/zoo.21323
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive behavior and hair cortisol levels in captive Dorcas gazelles (Gazella dorcas) as animal‐based welfare indicators

Abstract: Ensuring welfare in captive wild animal populations is important not only for ethical and legal reasons, but also to maintain healthy individuals and populations. An increased level of social behaviors such as aggression can reduce welfare by causing physical damage and chronic stress to animals. Recently, cortisol in hair has been advanced as a non-invasive indicator to quantify long-lasting stress in many species. The sensitivity of social behavior and hair cortisol concentration was evaluated in several gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…At first this seems counterintuitive, as a number of studies have reported that frequent exposure to agonistic social behavior is associated with higher HCCs (Feng et al, 2016; Salas et al, 2016; Tennenhouse et al, 2016; Yamanashi et al, 2016). One possible explanation is that individuals who receive high rates of aggression, which is common in the despotic society of rhesus macaques, may often be able to predict aggression before it begins, and predictability has been associated with lower cortisol responses (Galhardo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At first this seems counterintuitive, as a number of studies have reported that frequent exposure to agonistic social behavior is associated with higher HCCs (Feng et al, 2016; Salas et al, 2016; Tennenhouse et al, 2016; Yamanashi et al, 2016). One possible explanation is that individuals who receive high rates of aggression, which is common in the despotic society of rhesus macaques, may often be able to predict aggression before it begins, and predictability has been associated with lower cortisol responses (Galhardo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…One objective measure may be overt social behavior, such as measured frequencies of aggression and affiliation. In this regard, several recent studies have begun examining the relationships between aggression and HCCs in mammals (Feng et al, 2016; Salas et al, 2016; Tennenhouse et al, 2016; Yamanashi et al, 2016). However, even though affiliation plays a fundamental role in social organization in humans and non-human primates, little research has examined the relationship between affiliation and chronic HPA axis activation.…”
Section: Introductionmentioning
confidence: 99%
“…Though steroid hair testing has been developing for wider use over the past decade, our literature search showed that most wildlife and domestic animal studies only measured cortisol in hair. The validation of other steroids, such as testosterone, may provide additional information on topics such as reproductive ecology (Bryan et al, 2014), social status (Koren et al, 2006), potential growth (Mouritsen et al, 2014), and social behaviours (e.g., Finkler & Terkel, 2010;Salas et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have used hair cortisol to investigate the effects of social status (Koren & Geffen, 2009;Koren et al, 2006), social density (Dettmer, Novak, Meyer, & Suomi, 2014;Grigg, Nibblett, Robinson, & Smits, 2017;Salas et al, 2016), human disturbance (Agnew, Smith, & Fowkes, 2016;Bourbonnais, Nelson, Cattet, Darimont, & Stenhouse, 2013;Ewacha, Roth, Anderson, Brannen, & Dupont, 2017;Fourie et al, 2015;Lyons, Mastromonaco, Edwards, & Schulte-Hostedde, 2017), hunting (Bryan et al, 2015), diet (Bryan, Darimont, et al, 2013;Lafferty, Laudenslager, Mowat, Heard, & Belant, 2015), resource availability (Bryan et al, 2014), parasitism (Carlsson, Mastromonaco, Vandervalk, & Kutz, 2016), season (Di Francesco et al, 2017), and climate variability (Bechshøft et al, 2013;Fardi, Sauther F I G U R E 1 Procedure for analysis of steroid hormones in hair from wild and domestic animals. Typical steps include (1) initial hair prep (e.g., removal of follicles, sorting guard hairs from underfur), (2) washing (e.g., 1-3× with water and 1-3× with isopropanol), (3) cutting or grinding (optional), (4) weighing hair into a vial, (5) extraction of steroids from hair using a solvent (typically methanol), (6) separation of extract from hair matrix by centrifugation, and (7) analysis using EIA, RIA, or LC-MS/MS.…”
Section: Biological Validations and Applicationsmentioning
confidence: 99%
“…Due to spatial constraints captive environments have difficulty in providing the ideal setting for natural behaviour, such as hunting, resulting in welfare issues among captive animals (Morgan and Tromborg, 2007). Sometimes, animals in captivity exhibit abnormal behaviour such stereotypies (Vaz et al, 2017) or aggressiveness (Salas et al, 2016) due to poor welfare, as behaviour is an animal's "first line of defence" in response to environmental change, i.e., what animals do to interact with, respond to, and control their environment (Mench, 1998). Moreover, in literature, the pathologies affecting captive animals have been shown to be different from the ones affecting wild populations (Seeley et al, 2016;Strong et al, 2016).…”
Section: Introductionmentioning
confidence: 99%